Availability and proximity of natural habitat influence cropland biodiversity in forest biomes globally. Issue 8 (30th May 2022) - Outhwaite, Charlotte L.; Ortiz, A. Monica D.; Spooner, Fiona E. B.; Dalin, Carole; Newbold, Tim
Abstract: Aim: Agriculture is one of the greatest pressures on biodiversity. Regional studies have shown that the presence of natural habitat and landscape heterogeneity are beneficial for biodiversity in agriculture, but it remains unclear whether their importance varies geographically. Here, we use local biodiversity data to determine which local and landscape variables are most associated with biodiversity patterns and whether their association varies between tropical and non‐tropical regions. Location: Global terrestrial area in forest biomes. Major taxa studied: More than 21, 000 species of vertebrates, invertebrates, plants and other taxa. Methods: We used generalized linear mixed‐effects models to analyse the relationships between either community total abundance or species richness (derived from the PREDICTS database) and a number of site‐level (predominant land use and land‐use intensity) and landscape‐level variables (distance to forest, the percentage of natural habitat in the surrounding landscape, landscape homogeneity, the number of land‐cover types in the landscape, and total fertilizer application). We compared the associations of these variables with biodiversity in tropical and non‐tropical regions. Results: In most cases, changes in biodiversity associated with landscape‐level variables were greater than those associated with local land use and land‐use intensity. Increased natural habitat availability was associated with the most consistent increases in biodiversity. Landscape homogeneity was also important but showed different directions of biodiversity change between regions. Associations with fertilizer application or the number of land‐cover types were generally weaker, although still of greater magnitude than for the local land‐use measures. Main conclusions: Our results highlight similarities and differences in the association of local‐ and landscape‐scale variables with local biodiversity in tropical and non‐tropical regions. Landscape natural habitat availability had a consistent positive association with biodiversity, highlighting the key role of landscape management in the maintenance of biodiversity in croplands. Landscape‐scale variables were almost always associated with greater changes in biodiversity than the local‐scale measures.